2015
DOI: 10.1371/journal.pcbi.1004302
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Molecular Shape of Spectrin: A Compact Supercoil Resembling a Chinese Finger Trap

Abstract: The primary, secondary, and tertiary structures of spectrin are reasonably well defined, but the structural basis for the known dramatic molecular shape change, whereby the molecular length can increase three-fold, is not understood. In this study, we combine previously reported biochemical and high-resolution crystallographic data with structural mass spectroscopy and electron microscopic data to derive a detailed, experimentally-supported quaternary structure of the spectrin heterotetramer. In addition to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…To assess the distribution of spectrin within LSECs, we applied two‐colored dSTORM optical nanoscopy of spectrin and actin. Spectrin always forms heterotetramers (two alpha units and two beta units) . The mammalian alpha subunits are reportedly similar in molecular weight but are structurally distinct and share only limited immunologic cross reactivity .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the distribution of spectrin within LSECs, we applied two‐colored dSTORM optical nanoscopy of spectrin and actin. Spectrin always forms heterotetramers (two alpha units and two beta units) . The mammalian alpha subunits are reportedly similar in molecular weight but are structurally distinct and share only limited immunologic cross reactivity .…”
Section: Resultsmentioning
confidence: 99%
“…Spectrin's functional length is approximately 55 to 65 nm but can extend up to 200 nm, which makes it a perfect candidate to control the fenestrae in their open vs closed states. One could expect that the interaction between spectrin units and actin across the cell membrane is greatly facilitated at the cell periphery because the cell height is reduced and because of the presence of numerous short actin filaments.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this mechanoprotective role of the actin/spectrin scaffold, axons of C. Elegans worms lacking ß-spectrin progressively break when the animal is moving (Hammarlund et al, 2007). At rest, spectrin tetramers are~50-70 nm long, whereas in axons their~180 nm indicates that they are fully extended, and thus under tension like extended springs (Brown et al, 2015). FRET sensor probes inserted in ß-spectrin show that indeed, spectrins are extended and under tension along axons (Krieg et al, 2014), a finding confirmed by modeling of the axon mechanical properties (Lai and Cao, 2014;Y.…”
Section: Actin Ringsmentioning
confidence: 83%
“…2A). This spacing value corresponds to the length of individual, extended spectrin tetramers (Bennett et al, 1982;Brown et al, 2015): spectrin appear as periodic stripes along the axon when labeling the axonal ß2-spectrin and α2-spectrin, or the AIS-specific ß4-spectrin (Huang et al, 2017a, 2017b; Leterrier et al, 2015; Xu et al, 2013) ( Fig. 2B & 2C).…”
Section: Actin Ringsmentioning
confidence: 99%
“…15,16 Moreover, the physiological resting length of spectrin can undergo a 3-fold extension, which can be explained by a compact supercoil model. 17 Excluding the linker regions between SRs, a giant isoform of Nesprin-1 possesses 74 SRs and MSP300 at least 78 SRs 18 (our unpublished data). Thus, their static length should be more than 370 nm and the de facto total length under tension can be much longer.…”
Section: Nesprins Are Required For Tensional Homeostasis and Force Trmentioning
confidence: 90%